Climate Change : [electronic resource]: Environment and History of the Near East - 224231 Issar, Arie S.; Zohar, Mattanyah; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
01